Trends in Any and High-Dose Opioid Analgesic Receipt Among Aging Patients With and Without HIV. - Becker, William C; Gordon, Kirsha; Jennifer Edelman, E; Kerns, Robert D; Crystal, Stephen; Dziura, James D; Fiellin, Lynn E; Gordon, Adam J; Goulet, Joseph L; Justice, Amy C; Fiellin, David A (AIDS and behavior, 2015)
Harms of opioid analgesics, especially high-dose therapy among individuals with comorbidities and older age, are increasingly recognized. However, trends in opioid receipt among HIV-infected patients are not well characterized. We examined trends, from 1999 to 2010, in any and high-dose (≥120 mg/day) opioid receipt among patients with and without HIV, by age strata, controlling for demographic and clinical correlates. Of 127,216 patients, 64 % received at least one opioid prescription. Opioid receipt increased substantially among HIV-infected and uninfected patients over the study; high-dose therapy was more prevalent among HIV-infected patients. Trends in high-dose receipt stratified by three age groups revealed an increasing trend in each age strata, higher among HIV-infected patients. Correlates of any opioid receipt included HIV, PTSD and major depression. Correlates of high-dose receipt included HIV, PTSD, major depression and drug use disorders. These findings suggest a need for appropriate balance of risks and benefits, especially as these populations age.